Diversity of Bumblebees (Bombini, Apidae: Hymenoptera) in Chitwan Annapurna Landscape (CHAL) of Central Himalaya, Nepal - Ghimire, Kishor Chandra; Bhusal, Daya Ram (BMC Journal of Scientific Research, 2022)
Bumblebees (Hymenoptera: Apidae: genus Bombus Latreille, 1802) are the effective group of pollinators for various crops and wild plants in the north high-hills of Nepal. Over the past few decades, it has been expected that the population of these insects has declined since there are still unexplored areas and rich floral and faunal diversity. However, there are very few scientific publications as well as little researches have been carried out focusing on bumble bees in high-hills of Nepal. Therefore, this research was focused to explore the bumblebees in Chitwan Annapurna Landscape (CHAL) in Manang, Mustang and Gorkha districts with altitudinal gradients from 500 -2700 m asl from June to September 2019. The data were collected following accessible walking trails by opportunistic survey method and specimens were captured using sweeping net. Total 7 subgenera with 8 species of genus Bombus were identified. Bombus festivus (subgenus: Festivobombus) was the most dominant species. The diversity of bumblebee species was more in Gorkha site compared to the Manang and Mustang sites. Bombus haemorrhoidalis, B. eximus, and B. rotundiceps were the dominant species in Gorkha site, whereas B. festivus, B. lepidus, and B. tunicatus were dominant in Manang districts. Bombus festivus, B. tunicatus, and B. turneri were the most encountered species in Mustang. This study indicates that each district has the unique diversity of bumblebees particularly a site-specific variation of the Bombus species, which are likely to the variations in floral resources, microclimate and habitat types.